Development of tannic acid/chitosan/pullulan composite nanofibers from aqueous solution for potential applications as wound dressing. (22nd January 2015) - Xu, Fenghua; Weng, Baicheng; Gilkerson, Robert; Materon, Luis Alberto; Lozano, Karen
Highlights: Ternary composite nanofibers were mass produced by the forcespinning ® technique. The nanofibers were developed from aqueous solutions without organic solvents. The nanofibers have synergistic antibacterial activity. The ternary composite nanofibrous membranes favor cell attachment and growth. Abstract: This study presents the successful development of biocompatible tannic acid (TA)/chitosan (CS)/pullulan (PL) composite nanofibers (NFs) with synergistic antibacterial activity against the Gram-negative bacteria Escherichia coli. The NFs were developed utilizing the forcespinning ® (FS) technique from CS-CA aqueous solutions to avoid the usage of toxic organic solvents. The ternary nanofibrous membranes were crosslinked to become water stable for potential applications as wound dressing. The morphology, structure, water solubility, water absorption capability and thermal properties of the NFs were characterized. The ternary composite membrane exhibits good water absorption ability with rapid uptake rate. This novel membrane favors fibroblast cell attachment and growth by providing a 3D environment which mimics the extracellular matrix (ECM) in skin and allows cells to move through the fibrous structure resulting in interlayer growth throughout the membrane, thus favoring potential for deep and intricate wound healing.